Notary Role In The Process Of Establishment Limited Liability Company (PT) - Iqbal Rino Akta Pratama; Asep Suherdin; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study were 1) To determine the role of the notary in the process of setting up a Limited Liability Company (PT), 2) To determine whether the obstacles faced by the notary in the process of setting up a Limited Liability Company (PT) and the solution.The method used in this research is empirical juridical approach, juridical (legal viewed as the norm or das sollen), because in discussing the problem of research using legal materials (both the written law and the unwritten law or good legal materials primary or secondary law). Specifications research used in this research is descriptive, as explained, describe or disclose the legislation in force associated with the theories of law and positive law enforcement practice concerning these issues.Based on the results of this study concluded that 1) According to the Minister of Justice of the Republic of Indonesia No. M.01-PR.08.01 1996 on Procedures for Submission of Application and Approval of Deed of Establishment of the Limited Liability Company, that pengesahaan establishment of PT may be made by the founders together or proxies , can also by a notary, so there is no necessity notaries as public officials who approve their establishment of limited liability companies, but these roles can be carried out by the founder of the company. 2) Barriers faced delay problems often arise.For the notary, will make the process inefficient. Probes for the ongoing process difficult because of the lack of an online system that can monitor the manufacturing process. Solutions to overcome the obstacles faced by the notary in the legalization of the establishment Company Limited is a Limited Liability Company in the legalization of the establishment can be overcome with the Legal Entity Administration System electronically, as a matter of time and efficiency in monitoring the rights to this process.Keywords: Role; Notary Public; Limited Liability Company (PT)